LITERASI DIGITAL PEMBENTUK KEMAMPUAN BERNALAR KRITIS SISWA SEKOLAH DASAR DALAM MEMBEDAKAN FAKTA DAN OPINI - Intan Nastiti Hayu Laksita; Rian Nurizka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of digital literacy as a means to develop students’ critical thingking skills at Al Amin Sinar Putih Elementary School, with a focus on their ability to distinguish between facts and opinions. This research employs a qualitative approach, with research subjects including the school principal, homeroom teachers, ICT subject teachers, and students at Al Amin Sinar Putih Elementary School. Data were collected using the following techniques: a0 Observation method, b) Interview method, and c) Documentation method. The findings indicate that implementing digital literacy to foster students’ critical thingking requires thorough planning, encompassing teachers’ skill readiness, curriculum adaptation, and the provosion of supporting facilities and infrastructure. Futhermore, its execution must achieve learning objectives through methods, strategies, and media tailored to students’ needs, along with evaluations that assess program effectiveness and yield solutions to existing challenges. Through the integration of digital literacy in learning, students gain a better understanding of the benefits and risks of digital environments in everyday life, thereby enhancing their critical thingking skills in distinguishing facts form opinions, which aligns with current urgencies.